Acquisition of Sign Languages - and Lillo-Martin, Diane; Henner, Jonathan (Annual Review of Linguistics, 2021)
Natural sign languages of deaf communities are acquired on the same time scale as that of spoken languages if children have access to fluent signers providing input from birth. Infants are sensitive to linguistic information provided visually, and early milestones show many parallels. The modality may affect various areas of language acquisition; such effects include the form of signs (sign phonology), the potential advantage presented by visual iconicity, and the use of spatial locations to represent referents, locations, and movement events. Unfortunately, the vast majority of deaf children do not receive accessible linguistic input in infancy, and these children experience language deprivation. Negative effects on language are observed when first-language acquisition is delayed. For those who eventually begin to learn a sign language, earlier input is associated with better language and academic outcomes. Further research is especially needed with a broader diversity of participants.
Keywords: Björn-2026-02-22